Modification of FSE Method Based on Coefficients of Homogeneity - Karapetyan, Gevorg (Mathematical Problems of Computer Science, 2021)
In this paper a modification of frequency selective extrapolation (FSE) method is described. The FSE method is used for concealment of missing blocks in digital images. The modification of the method is based on missing block support area analysis with usage of Canny edge detection algorithm. In the result of the analysis, for each missing block a suboptimal support area size is selected, which is used in FSE method. The paper includes experimental results which are compared with the results of frequency FSE method.